Thriving, burnout, and coping strategies of early and later career counseling center psychologists in the United States. Issue 4 (1st October 2016) - Sim, Wonjin; Zanardelli, Gina; Loughran, Mary Jo; Mannarino, Mary Beth; Hill, Clara E.
Abstract : We interviewed seven early career psychologists (ECPs) and seven later career psychologists (LCPs) employed at university counseling centers in the United States about their experiences with thriving, burnout, and coping. We analyzed the data using Consensual Qualitative Research. Typical factors that contributed to thriving included recognition for achievement and the climate of counseling center and campus, although the latter was more important for ECPs than LCPs. Typical factors that contributed to burnout included challenges with tasks and responsibilities and challenges related to professional relationships. Finally, interpersonal support (general), self-care, cognitive strategies, and behavioral strategies (typical) were coping strategies used by both ECPs and LCPs, but only ECPs identified using personal therapy. Implications for counseling centers and for research are presented.